Economic relations after the Kennedy Round - Alting von Geusau, Frans Alphons Maria; Albregts, A. H. M.; Center for International Studies (John F. Kennedy Institute); Bernard van Leer Foundation (Leyden, A. W. Sijthoff, 1969)
The Kennedy round was a comprehensive negotiation. It attached simultaneously; but with different techniques, the various problems standing the way of world trade liberalization. It was organised by the John F. Kennedy Institute and sponsored by the Bernard van Leer Foundation.
Includes bibliographical footnotes.
osa 11/07/2018
Loans
Keywords: International economic relations